Lack of an Association between CYP11B2 C-344T Gene Polymorphism and Ischemic Stroke: A Meta-Analysis of 7,710 Subjects - Pi, Yan; Zhang, Li-li; Chang, Kai; Guo, Lu; Liu, Yun; Li, Bing-hu; Cao, Xiao-jie; Liao, Shao-qiong; Gao, Chang-yue; Li, Jing-cheng (PloS one, 2013)
The association between aldosterone synthase (CYP11B2) C-344T gene polymorphism and ischemic stroke remains controversial and ambiguous. To better explain the association between CYP11B2 polymorphism and ischemic stroke risk, a meta-analysis was performed. Based on comprehensive searches of Medline, Embase, Web of Science, CNKI and CBM databases, we identified and abstracted outcome data from all articles to evaluate the association between CYP11B2 polymorphism and ischemic stroke. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were performed in all genetic models. Fixed or random effects model was separately used depending on the heterogeneity between studies. Publication bias was tested by Begg's funnel plot and Egger's regression test. A total of 12 studies including 3,620 ischemic stroke cases and 4,090 controls were identified. There was no statistical evidence of association between CYP11B2 C-344T polymorphism and ischemic stroke in all genetic models (allelic model: OR = 1.19, 95% CI = 0.95-1.49; additive model: OR = 1.43, 95% CI = 0.91-2.27; dominant model: OR = 1.30, 95% CI = 0.89-1.89; and recessive model: OR = 1.24, 95% CI = 0.96-1.60). On subgroup analysis by ethnicity, similarly results were found in both Asians and non-Asians. For Asians, the combined ORs and 95% CIs were (allelic model: OR = 1.07, 95% CI = 0.87-1.32; additive model: OR = 1.15, 95% CI = 0.77-1.71; dominant model: OR = 1.13, 95% CI = 0.92-1.38; and recessive model: OR = 1.09, 95% CI = 0.84-1.40). For none-Asians, the combined ORs and 95% CIs were (allelic model: OR = 1.58, 95% CI = 0.90-2.76; additive model: OR = 2.37, 95% CI = 0.79-7.05; dominant model: OR = 1.79, 95% CI = 0.77-4.19; and recessive model: OR = 1.80, 95% CI = 0.96-3.36). The present meta-analysis suggested that CYP11B2 C-344T polymorphism was unlikely contribute to ischemic stroke susceptibility.